Perencanaan Sistem Informasi Produksi Kapal Baru Berbasis Android di Industri di Galangan - Kalam Nur Alif; Erifive Pranatal; Minto Basuki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Shipyards are often difficult to find information quickly and efficiently on every component of the workplace. A good information system is actually needed for the work process in the shipyard because the project head's planning for the distribution of the project workload being carried out will result in a smooth production process, which will affect the completion time of the work to be carried out. Each of these stages is the final result stage where at this stage the author will draw conclusions to answer the formulation of the packing report based on writing which is prone to loss and damage. The development of an android-based ship repair information system that can be used to quickly and accurately report data required by the central supervisor allows for full monitoring of the new ship building process, which is standard practice in many shipyards that have a research methodology to solve the problem.